ANALISIS SKALA EKONOMIS DAN EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHA PERKEBUNAN KAKAO DI KECAMATAN MENDOYO - Handyliani, Ni Made Dwi; Meydianawati, Luh Gede (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 11, November 2018 (pp. 2309-2548), 2018)
The purpose of this study are to analyze  economies of scale and to analyze the efficiency of production factors in the plantation business of Cocoa in the district of Mendoyo Jembrana regency. The type of data in this research is quantitative and qualitative data with primary and secondary data source. Data analysis techniques used in this study are Cobb-Douglas analysis techniques, economies of scale and economic efficiency. Respondents in this study amounted to 79 people from 371 samples of farmers in 9 Subak Abian calculated using Slovin formula. Determination of the number of research samples in each subak is determined by the proportionate statified random sampling method. The results showed that the variable of land area, capital, the use of pesticide and labor  simultaneously and partial have significant effect on the amount of cocoa production (Y) in dictrict of Mendoyo Jembrana regency. The economies of scale test are in an increasing return of scale condition with the use of production factors that are still in inefficient condition. Keywords: Total production, economic of scale, efficiency of production factors